(untitled) (Research, Society and Development, 2021)
Among oilseeds, sesame has functional components that increase resistance against oxidative deterioration, providing neutraceutical values. Considering the high nutritional and functional potential of the sesame extract or "milk", it is necessary to apply conservation techniques that increase its shelf life and give rise to new products. Many drying processes have been used for the production of powdered foods, among which freeze-drying is highlighted. In this context, the technology applied in the development of a new product from sesame extract (sesame milk), pre-frozen under different temperatures (-20, -60, -100 and -140 ° C) was studied, addressing the heat and mass transfer in freeze drying of this product, introducing new concepts proposed by Cavalcanti-Mata (2018) from the Fick model, giving new meaning to the equations proposed by Page, Lewis and Cavalcanti Mata. Among the drying models studied, the Cavalcanti-Mata modified by Cavalcanti-Mata was the one that best expressed the experimental data. In the models by Fick, Cavalcanti-Mata, Page and Lewis modified by Cavalcanti-Mata, the diffusion of the sublimation of the sesame extract or “milk” decreased proportionally the decrease in the pre-freezing temperature of the samples. Enthalpy and entropy grew with the decrease in the pre-freezing temperature and Gibbs free energy was positive for the entire temperature range, having a behavior directly proportional to the decrease in the pre-freezing temperature, thus demonstrating that it is a non-spontaneous process.